MODIFIED ALVARADO SCORE IN CHILDREN WITH DIAGNOSIS OF APPENDICITIS - PEYVASTEH,Mehran (2017)
ABSTRACT Background: Appendicitis is one of the most common abdominal emergency. Some predictive scoring systems are recommended to decrease the rate of negative appendectomy. Aim: To evaluate sensitivity, specificity, positive predictive value, and negative predictive value of modified Alvarado score in children who underwent appendectomy. Methods: Four hundred children with initial diagnosis of appendicitis were randomly selected from patients who underwent appendectomy. Modified Alvarado score was used for evaluation of the appendicitis, that was confirmed using histology. Results: Of modified Alvarado score components, anorexia; nausea and vomiting and rebound tenderness were significantly more common in children with positive appendectomy in contrast to patients with negative appendectomy. Sensitivity, specificity, positive predictive value, and negative predictive value for modified Alvarado score were: 91.3%; 38.4%; 87.7%; and 51.2% respectively. Conclusion: Alvarado score has high sensitivity but low specificity for diagnosis of acute appendicitis in children.